Structure-Guided Designing and Evaluation of Peptides Targeting Bacterial Transcription - Kaur, Gundeep; Kapoor, Srajan; Kaundal, Soni; Dutta, Dipak; Thakur, Krishan Gopal (Frontiers in Bioengineering and Biotechnology, 2020)
The mycobacterial RNA polymerase (RNAP) is an essential and validated drug target for developing antibacterial drugs. The β-subunit of Mycobacterium tuberculosis (Mtb) RNAP (RpoB) interacts with an essential and global transcription factor, CarD and confers antibiotic and oxidative stress resistance to Mtb. Compromising the RpoB/CarD interactions results in the killing of mycobacteria, hence disrupting RpoB/CarD interaction has been proposed as a novel strategy for the development of anti-tubercular drugs. Here, we describe the first approach to rationally design and test the efficacy of the peptide-based inhibitors which specifically target the conserved PPI interface between bacterial RNAP β/transcription factor complex. We performed in silico protein-peptide docking studies along with biochemical assays to characterize the novel peptide-based inhibitors. Our results suggest that the top-ranked peptides are highly stable, soluble in aqueous buffer and capable of inhibiting transcription with IC50 >50 µM concentration. Using peptide-based molecules, our study provides the first evidence to target the conserved RNAP β/transcription factor interface for designing new inhibitors. Our results may hence form the basis to further improve the potential of these novel peptides in modulating bacterial gene expression thus inhibiting bacterial growth and hence combating bacterial infections.